Added value of 3D-DRIVE and SWI Magnetic Resonance Imaging Sequences in Intraventricular Neurocysticercosis (IVNCC): An Institutional Experience from Northeast India - Boruah, Deb K.; Gogoi, Bidyut Bikash; Das, Kuntal Kanti; Sarma, Kalyan; Phukan, Pranjal; Singh, Binoy Kumar; Hazarika, Karuna; Jaiswal, Awadhesh (Acta medica Lituanica, 2021)
Background: Prompt diagnosis and early treatment institution are important in intraventricular neurocysticercosis(IVNCC) as compared to the parenchymal or racemose form because it is associated with a poorer patient prognosis. Intraventricular neurocysticercosis is often missed on CT scan or conventional cranial magnetic resonance imaging because of similar density or signal intensity of cysticercus lesion with cerebrospinal fluid. Thestudy aims to evaluate the added value of 3D-DRIVE and SWI MRI sequences in isolated intraventricular cysticercosis with acute neurological presentation. Methods and Materials: This retrospective study was carried out on diagnosed 10patients with isolated intraventricular neurocysticercosis(IVNCC) presented to a tertiary care hospital with an acute onset of symptoms or acute neurological deficit between June 2019 to May 2021. Relevant neurological examination, CSF analysis, a serological test of neurocysticercosis and MRI scan of the brain were performed. Result: Tenpatients of isolated intraventricular neurocysticercosis (3 males and 7 females) having 3 pediatric and7 adults were included in this study sample.The common neurological complications of the isolated intraventricular neurocysticercosis in this study are observed as obstructive hydrocephalus in 8(80%) patients and ependymitis in 7(70%) patients.IVNCC with distinctly visualized scolex (visibility score 2) identified in 2(20%) patients in T2WI, 8 (80%)patients in 3D-DRIVE and 3(30%) patients in SWI sequences. The cyst wall of IVNCC was distinctly visualized (visibility score 2) in 1(10%) patient in T2WI, 8(80%) patientsin 3D-DRIVE and 6(60%) patients in SWI sequence. Conclusion: Heavily T2-weighted steady-state and SWI sequences should be added to routine MRI sequences that helps to identify IVNCC and should be used in patients with unexplained hydrocephalus, especially in endemic regions of Neurocysticercosis.